MITF controls the TCA cycle to modulate the melanoma hypoxia response. (8th July 2019) - Louphrasitthiphol, Pakavarin; Ledaki, Ioanna; Chauhan, Jagat; Falletta, Paola; Siddaway, Robert; Buffa, Francesca M.; Mole, David R.; Soga, Tomoyoshi; Goding, Colin R.
Abstract: In response to the dynamic intra‐tumor microenvironment, melanoma cells adopt distinct phenotypic states associated with differential expression of the microphthalmia‐associated transcription factor (MITF). The response to hypoxia is driven by hypoxia‐inducible transcription factors (HIFs) that reprogram metabolism and promote angiogenesis. HIF1α indirectly represses MITF that can activate HIF1α expression. Although HIF and MITF share a highly related DNA‐binding specificity, it is unclear whether they co‐regulate subset of target genes. Moreover, the genomewide impact of hypoxia on melanoma and whether melanoma cell lines representing different phenotypic states exhibit distinct hypoxic responses is unknown. Here we show that three different melanoma cell lines exhibit widely different hypoxia responses with only a core 23 genes regulated in common after 12 hr in hypoxia. Surprisingly, under hypoxia MITF is transiently up‐regulated by HIF1α and co‐regulates a subset of HIF targets including VEGFA . Significantly, we also show that MITF represses itself and also regulates SDHB to control the TCA cycle and suppress pseudo‐hypoxia. Our results reveal a previously unsuspected role for MITF in metabolism and the network of factors underpinning the hypoxic response in melanoma.